2009
DOI: 10.5005/jp-journals-10007-1004
|View full text |Cite
|
Sign up to set email alerts
|

Herniotomy in Infants, Children and Adolescents without Disruption of External Ring

Abstract: Inguinal hernia is one of the commonest pediatric surgical problems and when treated early and appropriately is associated with negligible morbidity and very rarely any mortality. In our prospective study we introduce a new method for repair of hernia in infants, children and adolescences without disruption of external ring. Our study involves 252 patients with inguinal hernia, the ages ranging from 7 days to 15 years, 8 female and the remaining male. We apply the principles of minimal access surgery but witho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…11 Kareem AA et al study was done to evaluate minimal access surgery without laparoscopy in which herniotomy was done without disturbing the external ring and keeping the incision size less than 1 cm. 16 The study concluded that laparoscopic surgery is not the most superior minimally invasive surgical technique for inguinal hernia and herniotomy can be done in a less invasive manner with low cost and fewer complications while maintaining surgeon's tactile sensation with a delicate and pleasurable surgery.…”
Section: Discussionmentioning
confidence: 97%
“…11 Kareem AA et al study was done to evaluate minimal access surgery without laparoscopy in which herniotomy was done without disturbing the external ring and keeping the incision size less than 1 cm. 16 The study concluded that laparoscopic surgery is not the most superior minimally invasive surgical technique for inguinal hernia and herniotomy can be done in a less invasive manner with low cost and fewer complications while maintaining surgeon's tactile sensation with a delicate and pleasurable surgery.…”
Section: Discussionmentioning
confidence: 97%
“…There was nearly fourth 21.7% of children in control group had wound discharge compared to none in study group, where 69.2% of children in control group had Serogenouse discharge and 15.4% of children had pus and blood discharge. Table ( 9): Presents the relationship between the studied children regarding to their post-operative complications. There was high significant difference as the P Values were equal <0.001** where in the third day of operation there was more than two thirds of children 70% in study group who had scrotal swelling compared to the majority of children 96.7% in control group.…”
Section: Table (8)mentioning
confidence: 99%
“…In infants due to inguinal hernia ring tight, there is a high risk of hernia incarceration. 2 The incidence is highest during the first year of life and then gradually decreases thereafter, so one third of children undergoing surgery for hernia are less than six months of age. Premature infants have an even higher risk of developing inguinal hernia with incidence of 9-11 and 35-55% of these cases are bilaterally.…”
Section: Introductionmentioning
confidence: 99%